Análisis socio-ambiental de los ecosistemas de la laguna de Yambo, cantón Salcedo, provincia de Cotopaxi 2021. - Bautista Barreros, Madeley Cecibel (2021)
The Yambo lagoon has a large number of ecosystems, which have been affected by various factors such as: the expansion of the agricultural frontier, tourism, anthropic activities, hunting and fishing, for this reason the research project on socio-economic analysis was carried out. - environmental of the ecosystems of the Yambo lagoon, it is worth mentioning that the research study was also born at the request of the Autonomous Decentralized Municipal Government of the canton Salcedo, a strategic ally, in order to identify, evaluate the loss and degradation of ecosystems within the lagoon and propose alternatives for the conservation, protection and care of this natural charm; For the development of the research project, a descriptive research was used, which helped to recognize and determine the study area, in the same way the qualitative quantitative research was applied since it was oriented to the description of the physical, hydric, biotic and socio-environmental of the study area, through techniques such as observation and survey, it was evidenced that the main factors that affect the changes in the lagoon are the increase in tourist activities, operation of motor boats of more 45 Hp, sewage and runoff discharges directly into the lagoon. Among the environmental factors analyzed and evaluated, the one that most influences the loss of the environmental quality of this ecosystem and its contamination is the lack of oxygen for the survival of aquatic and plant life since Dissolved Oxygen is 76.85 % saturation. In addition, it can be mentioned that the soil of the Yambo lagoon is alkaline because its pH is 8.6, this has led to an increase in electrical conductivity, causing the drought of the ecosystem. In the study place, 58 plant species of flora were identified that are in a good state of conservation, the most representative fauna of the place are birds, having a total of 45 species, which is in a bad state of conservation, a situation presented by of the various environmental and anthropogenic problems that occur in the lagoon. In the social uprising, it is evident in the Yambo lagoon that there is no sewerage network, which means that tour operators have a septic tank, no health centers are observed within the area of direct influence, the majority of the population It is of a mixed race, a second order path is used to enter the lagoon, 5% of the population of direct influence cannot read, in the Yambo lagoon the existence of the semi-humid Equatorial Mesothermic climate is observed located in the southern part of the parish and the dry Mesothermic Equatorial climate, which covers most of the territory.